Comparative evaluation of Nickel and Lead scavenging efficiency by in-vivo grown Plants using atomic absorption spectroscopy - Ruchi Bhadoria; Sunita Sharma (International Journal of Phytomedicine, 2014)
Phytoextraction, the use of hyperaccumulator plant species to scavenge toxic heavy metals from contaminated soils are considered as an emerging technique for cost effective and environment friendly detoxification. The present study was conducted to evaluate and compare the scavenging efficiency of in-vivo grown climber plants, that is Cvcitmis sativus, Armenian cucumber, Lufa acutangula, Momordica charantia descourt and Lagenaria siceraria for the uptake of Nickel and lead using atomic absorption spectroscopy (AAS). Bioassays of field grown (In-vivo) plants were subjected to atomic absorption spectrophotometer for the analysis of scavenging efficiency of the aforementioned elements, after 98 days of growth in soils, contaminated with each of these, separately. The in-vivo grown climber plants absorbed much lesser amounts of Ni, that is, 0.79, 1.05, 0.45 and 1.61 ppm as compared to Pb plants which showed higher ranges of uptake, that is, 2.09, 10.39, 4.77 and 8.29 ppm, respectively. The metal uptake ratios were proportional to their concentrations in the contaminated soils. Maximum uptake for heavy metals was observed by the roots in all plants. Nodes also showed high heavy metal accumulation in the aerial region. Higher concentration of heavy metals in the soil showed a negative effect on their growth.